Integrating Planning and Environmental Protection: An Analysis of post-Brexit Regulatory Styles and Practitioner Attitudes in the UK. (7th August 2020) - Cowell, Richard; Ellis, Geraint; Fischer, Thomas; Jackson, Tony; Muinzer, Thomas; Sykes, Olivier
ABSTRACT: Debates around the impacts of the UK's exit from the European Union ('Brexit') have exposed the limited critical attention given to how planning systems intersect with environmental protection. This is an important omission, especially given deregulatory pressures on both planning and environment in many countries. In response, this paper uses documentary, interview and focus group data, to conceptualise different regulatory styles governing the environment-planning interface, and assess UK planning practitioner attitudes to EU environmental legislation and scenarios for future change. The data show practitioners largely supporting the fixed standards and robust oversight characteristic of EU environmental regulatory styles, anxious about deregulation, and interested in procedural flexibility. More fundamentally, it also reveals the compromises struck in regulatory design, and the importance of concrete development-environment challenges in constructing arguments for change. Consequently, planning occupies a pivotal position within wider debates about new environmental policy fixes, warranting more extensive professional discussion.